2020
DOI: 10.1177/0091450920941267
|View full text |Cite
|
Sign up to set email alerts
|

Governing Parental Drug Use in the UK: What’s Hidden in “Hidden Harm?”

Abstract: In 2003, the UK Advisory Council on the Misuse of Drugs published Hidden Harm, the product of an inquiry that exposed the “problems” of parental drug use and its neglect by professionals. It outlined an extensive program of reforms designed to protect children from harm. Despite its far-reaching influence, it has rarely been subject to scrutiny, with analyses focusing on its impact instead. Drawing on Bacchi’s post-structuralist “What’s the Problem Represented to be” approach, we examine problematizations with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
1
8
0
Order By: Relevance
“…Theme 4 focused directly on participants’ views about social workers’ professional practice, which included the views that social workers should work more collaboratively with parents; that there should be more continuity and fewer staff changes; that social services should make greater efforts to keep families together; that goals and deadlines should be more realistic; that social workers should avoided shaming in their communication; that social workers should focus more on parenting skills and less on drug use; and that drug treatment programmes themselves should be more effective. This is consistent with calls for more genuine collaboration with parents who use drugs, and for policy and practice to move away from individualised risk-based models and towards public health models of childcare and protection (Whittaker et al , 2020).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Theme 4 focused directly on participants’ views about social workers’ professional practice, which included the views that social workers should work more collaboratively with parents; that there should be more continuity and fewer staff changes; that social services should make greater efforts to keep families together; that goals and deadlines should be more realistic; that social workers should avoided shaming in their communication; that social workers should focus more on parenting skills and less on drug use; and that drug treatment programmes themselves should be more effective. This is consistent with calls for more genuine collaboration with parents who use drugs, and for policy and practice to move away from individualised risk-based models and towards public health models of childcare and protection (Whittaker et al , 2020).…”
Section: Discussionsupporting
confidence: 76%
“…The view that parental substance use is almost inherently harmful to children has been challenged since the publication of the Hidden Harm report (Whittaker et al , 2020), and it has been recognised that having a secure parental relationship can be a significant protective factor for children of substance using parents (Dawe and Dawe, 2007). Best (2012) argued for a general transformation of drug treatment in which “mutual aid groups”, owned and directed by the members, bridge the gap between clients and professionals.…”
Section: Introductionmentioning
confidence: 99%
“…This study provides insight in mechanisms that may contribute to feelings of loneliness, shame, social isolation, low self-esteem and lack of social support experienced by children of parents with SUDs (97)(98)(99)(100). In this sense, the effects of secondary stigma became apparent for those relatives who are associated with stigmatized individuals, including parents with SUDs (101)(102)(103)(104)(105). It may be prudent to note that in this sample, parents did not receive substance use treatment during offspring's childhood and adolescence, what may possibly be explained by, amongst others, the impact of stigma and discrimination on parents' willingness to seek help and preventing access to treatment (103,106,107).…”
Section: Discussionmentioning
confidence: 94%
“…Given the disruptive effect of stigma on family cohesion in families with parental substance use, with relatives often experiencing to be "invisible" (99), this study emphasizes the need for applying a developmental and interactional perspective on social support to children and parents with SUDs, as stated by Newcomb ((110), p. 54): "Social support can no longer be considered strictly an external force impinging upon the individual; rather, it must be viewed as an evolving developmental and interactive process between an individual and his or her social environment." Although children of parents with SUDs experience need for connectedness and receiving social support from trusted adults (97,111), which has been shown to be protective in this group of children at-risk (112), feelings of shame and self-blame related to the upbringing may hamper help-seeking in children, with implications for long-term mental and physical health (104,113,114). Previous studies showed that also among parents with SUDs, other mental health difficulties often co-occur (115).…”
Section: Discussionmentioning
confidence: 99%
“…A special issue of the International Journal of Drug Policy highlighted different applications of the WPR ‘problematisation’ framework as an analytical approach to the study of drug policy (Houborg et al., 2020, Denmark). In the UK, this research is related to the policy production of vulnerable subjects (Brown and Wincup, 2020), the governing of parental drug use (Whittaker et al., 2020) and constructions of dangerous drug-using mothers (Flacks, 2019). This analysis from the UK focused on health, drugs and child protection, and how ‘the problem of parental drug use is framed’ in policy documents, such as Hidden Harm, Three Years On (2003) and all government drug strategies since 1995 (Flacks, 2019).…”
Section: What Is the Problem Represented To Be? Wpr Policy Analysis F...mentioning
confidence: 99%